'I've got a gut feeling that I'd regret not choosing Spanish'. A critical discourse analysis of language option choice discussions on Mumsnet and Studentroom. Issue 5 (2nd September 2020) - Lanvers, Ursula; Lambrechts, Agata A.; Crosswaite, Madeline
ABSTRACT: Like other anglophone countries, the UK is experiencing a language 'crisis', in that fewer and fewer students opt to study a foreign language (FL) beyond the compulsory phase, and that the UK's language skills do not match its economic needs. Despite strong statements of commitments to increase FL uptake, decline in FL uptake in the UK's four nations persists. In a novel approach, this study investigates how key stakeholders (parents, students) discuss whether to continue with FL study beyond the compulsory phase on the internet platforms Mumsnet and Studentroom . The researchers undertook a thematic analysis of threads relevant to this topic on these platforms, in two equal-sized corpora from Mumsnet and Studentroom respectively. The analysis of stakeholders' stances towards both current, and wished for, FL policies and practices is then utilised to formulate five FL policy suggestions that respect stakeholders' preferences and concerns, and could lead to facilitating the choice for a FL beyond the compulsory phase.